1996
DOI: 10.3109/00016349609055025
|View full text |Cite
|
Sign up to set email alerts
|

Fetal exposure to tobacco smoke products: A comparison between self‐reported maternal smoking and concentrations of cotinine and thiocyanate in cord serum

Abstract: Cord serum cotinine and thiocyanate concentrations are related to daily smoking rate during pregnancy, but these concentrations vary considerably among occasional smokers. Detailed information on smoking habits is the key issue in understanding the adverse fetal effects of occasional smoking during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 20 publications
2
58
1
Order By: Relevance
“…We evaluated the validity of questionnaire information by using the levels of cotinine and thiocyanate in umbilical cord serum in 202 randomly selected mothers. There was an excellent agreement between high and low levels of biomarkers and daily and nonsmoking mothers (25).…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…We evaluated the validity of questionnaire information by using the levels of cotinine and thiocyanate in umbilical cord serum in 202 randomly selected mothers. There was an excellent agreement between high and low levels of biomarkers and daily and nonsmoking mothers (25).…”
Section: Methodsmentioning
confidence: 75%
“…The exposure information was collected before the onset of the outcome of interest, so any bias due to awareness of the disease of interest was avoided. We evaluated the questionnaire information on maternal smoking by biomarker concentrations in cord serum and found that smoking habits were reported accurately (25).…”
Section: Discussionmentioning
confidence: 99%
“…Questionnaire information on maternal smoking at the end of pregnancy was compared with biomarkers in umbilical cord serum taken at birth for 202 randomly selected mothers [35]. An excellent agreement was shown, which indicated that the mothers reported their smoking habits correctly.…”
Section: Discussionmentioning
confidence: 99%
“…Among children, salivary and urinary cotinine levels have been shown to rise with the number of smoking parents in the home [31,38], and in infants, urinary cotinine levels increased with the number of cigarettes smoked by the mother during the previous 24 h [67]. Among 202 newborns, the cord serum level of cotinine was significantly linearly related to the average daily number of cigarettes smoked by the mother during pregnancy [68]. The cotinine levels measured in nonsmokers exposed to ETS have ranged from less than 1% to about 8% of the levels measured in active smokers [5,69].…”
Section: Biomarkersmentioning
confidence: 99%